Determinan dan Strategi Peningkatan Pertumbuhan Ekonomi di Kota Jambi - Muhammad Ilham Irwansyah; Erni Achmad; Zainul Bahri (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research is entitled Determinants and Strategies of Enhancing Economic Growth in Jambi City. The objectives of this research are: (1) to analyze the conditions of economic growth, population, infrastructure, Human Development Index (HDI), investment, and capital expenditure in Jambi City; (2) to examine the effects of population, infrastructure, HDI, investment, and capital expenditure on economic growth in Jambi City; and (3) to formulate strategies to enhance economic growth in Jambi City. The results of the study indicate that there is a relationship between the population, infrastructure, HDI, investment, and capital expenditure with economic growth in Jambi City period 2004-2023 with percentage of contribution on 69.12%. Based on multiple linear regression analysis, these variables collectively have a significant and positive effect on economic growth in Jambi City during the 2004–2023 period. Partially, population, HDI, investment, and capital expenditure show a significant and positive influence, while infrastructure has a positive but not significant effect. Using the Analytical Hierarchy Process (AHP), the recommended strategies for enhancing economic growth in Jambi City include the development of basic infrastructure, facilitation of investment, support for regional leading sectors and UMKM, and human resource development.